Pobreza multidimensional y pobreza monetaria en Bolivia - Ernesto Bernal Martínez; Erika Soliz Cuevas (Institute for Advanced Development Studies (INESAD), 2025)
– In recent years, Bolivia has made progress in terms of poverty reduction; however, many households still live with low incomes or face deprivations in other aspects. For this reason, this study aims to estimate the evolution of poverty, both in multidimensional and monetary terms, as well as the effects of income growth and distribution in Bolivia from 2015 to 2022. The Alkire and Foster (2011) methodology is employed to calculate multidimensional poverty. To estimate monetary poverty, the poverty line method is used, and the effects of growth and distribution are evaluated using the Datt and Ravallion (1992) methodology. Results show that, although multidimensional poverty decreased between 2015 and 2022, about 45% of households in the country suffer simultaneous deprivations related to non-monetary aspects. Regarding monetary poverty, it decreased from 38.6% to 37.2% between 2015 and 2019; it increased to 39% in 2020, and then decreased to 38.1% in 2022. The most significant result of the income growth and distribution effect shows that poverty in Bolivia is more sensitive to economic growth.
Keywords: I3; I32; F43; 330; Poverty; Growth; Distribution; Multidimensional Poverty